HUBUNGAN OBESITAS PADA KEHAMILAN DENGAN BERAT BAYI DAN USIA KEHAMILAN SAAT PERSALINAN DI PUSKESMAS CAKRANEGARA - I Dewa Bagus Ketut Widya Pramana; Ario Danianto; Rifana Cholidah (Faculty of Medicine Universitas Mataram, 2022)
Background: Obesity is a fat metabolism disorder arised from the accumulation of excess fat in adipose tissue. The over accumulated fat in adipose tissue, results in an increases in the secretion of inflammatory cytokines that might hazardous to the health of maternal and infant. Increased inflammatory cytokines can leads to impaired hypothalamic-pituitary-axis, myometrial contractility and cervical ripening associated with gestational age at birth. Futhermore, the increase in inflammatory cytokines also causes an increase in the placental amino acid transport system and decreased placenta growth factor which is correlated with infant birth weight. Methods: This is a retrospective cohort study collecting cohort data of pregnant women that had met the inclusion and exclusion criteria at the Puskesmas Cakranegara from 2019 to 2021. The sampling method used in this study is total sampling. Results: There were 243 data maternal pregnancy that met the inclusion. There was a statistically significant correlation between BMI of pregnant women at first trimester and gestational age at delivery (p=0.032). There was also a statistically significant relationship between obesity in pregnancy and the incidence of preterm (p=0.029) and postmaturity (p=0.047). Otherwise, researcher didn’t find any statistical correlation between BMI of pregnant women measured in the first trimester and birth weight (p=0.066). Keyword: body mass index, obesity, gestational age, birth weight